2022
DOI: 10.3390/ijms232214307
|View full text |Cite
|
Sign up to set email alerts
|

Isosorbide Fatty Acid Diesters Have Synergistic Anti-Inflammatory Effects in Cytokine-Induced Tissue Culture Models of Atopic Dermatitis

Abstract: Atopic dermatitis (AD) is a chronic disease in which epidermal barrier disruption triggers Th2-mediated eruption of eczematous lesions. Topical emollients are a cornerstone of chronic management. This study evaluated efficacy of two plant-derived oil derivatives, isosorbide di-(linoleate/oleate) (IDL) and isosorbide dicaprylate (IDC), using AD-like tissue culture models. Treatment of reconstituted human epidermis with cytokine cocktail (IL-4 + IL-13 + TNF-α + IL-31) compromised the epidermal barrier, but this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 108 publications
0
1
0
Order By: Relevance
“…The leakage of LDH from keratinocytes may be induced by the intracellular accumulation of reactive oxygen species (ROS) associated with increased mitochondrial activity. 44,45 Since IL-17A induces nuclear translocation of transcription factor NF-E2-related factor 2 (Nrf2) and Nrf2-dependent expression of heme oxygenase-1 (HO-1) 46 which suppresses accumulation of ROS in keratinocytes, upadacitinib-induced decrease of endogenous IL-17A might lead to the downregulation of Nrf2/HO-1 pathway, inducing accumulation of ROS, which activates inflammasome cascade and resultant release of cytoplasmic LDH. 47,48 The reversal of IgE level after clinical improvement by upadacitinib treatment may be mediated by upadacitinib-induced inhibition of IL-21-mediated JAK1/JAK3/STAT3 pathway 24 since IL-21 suppresses IgE class switch recombination in human B cells through this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The leakage of LDH from keratinocytes may be induced by the intracellular accumulation of reactive oxygen species (ROS) associated with increased mitochondrial activity. 44,45 Since IL-17A induces nuclear translocation of transcription factor NF-E2-related factor 2 (Nrf2) and Nrf2-dependent expression of heme oxygenase-1 (HO-1) 46 which suppresses accumulation of ROS in keratinocytes, upadacitinib-induced decrease of endogenous IL-17A might lead to the downregulation of Nrf2/HO-1 pathway, inducing accumulation of ROS, which activates inflammasome cascade and resultant release of cytoplasmic LDH. 47,48 The reversal of IgE level after clinical improvement by upadacitinib treatment may be mediated by upadacitinib-induced inhibition of IL-21-mediated JAK1/JAK3/STAT3 pathway 24 since IL-21 suppresses IgE class switch recombination in human B cells through this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that the expression of IL-31 in peripheral blood lymphocytes of AD patients is increased, and the expression level is linearly correlated with the severity of the disease [17]. Th2 cells release IL-31 in the acute phase, which, after binding to IL-31 receptor A and activating STAT3 in EOS, can delay the apoptosis of EOS and significantly increase the secretion of proinflammatory cytokines and chemokines, leading to the development of AD lesions with skin barrier breakdown and transeptocutaneous water loss [18,19]. The damage of skin barrier function in AD increases the number of environmental irritants and allergens penetrating into the skin, leading to the aggravation and recurrence of inflammation or allergic reactions.…”
Section: Th2 Cellsmentioning
confidence: 99%